Toward an understanding of dwell fatigue damage mechanism of bimodal Ti-6Al-4V alloys. (10th May 2022) - Zeng, L.R.; Lei, L.M.; Luo, X.M.; Zhang, G.P.
Highlights: Pure fatigue and dwell fatigue properties of bimodal Ti-6Al-4 V alloys with different volume fractions of primary α phase were investigated. The local plastic deformation and damage extent of the primary and secondary α phases were quantitatively characterized by quasi- in-situ testing. A stress relaxation-based model was proposed to describe the microscopic damage process under dwell fatigue loading. Abstract: Dwell fatigue effect is a long-standing problem threatening the long-term service reliability for fan blades and fan disks of an aircraft engine. To understand the basic mechanism of dwell fatigue damage, pure fatigue and 60 s dwell fatigue properties of bimodal Ti-6Al-4V alloys with different volume fractions of the primary α (αp ) phase were examined comparatively. The results showed that both pure fatigue and dwell fatigue life decreased with increasing the volume fraction of the αp phase and the dwell fatigue life was lower than the pure fatigue one. The quasi- in-situ test results and the quantitative characterization of damage behaviors of the local microstructure units defined by the αp -secondary α (αs ) combination reveal that the αs phase close to the αp phase with extensively slip activities was gradually damaged under dwell fatigue loading, while that under pure fatigue loading was undamaged, demonstrating that the dwell loading induced the damage of the αs phase, and further reduced the fatigue life. A stress relaxation-based model is proposed to describe the physical mechanism on dwell fatigue damage of the bimodal Ti-6Al-4V alloy, i.e. the elastic deformation of the αs phase caused by the strain incompatibility would be gradually transformed into plastic deformation during the dwell stage, and thus promotes fatigue damage. The model provides new insights into the microscopic process of stress/strain transfer between the soft and hard microstructure units under dwell fatigue loading. Graphical Abstract: Graphical Abstract Image, graphical abstract .